2013
DOI: 10.1007/s10140-013-1123-y
|View full text |Cite
|
Sign up to set email alerts
|

Iranian 2012 earthquake: the importance of Focused Assessment with Sonography for Trauma (FAST) in assessing a huge mass of injured people

Abstract: The 2012 Iranian earthquakes took place in the cities of Ahar and Varzqan in East Azerbaijan province, on August 11, 2012, at 16:53 Tehran time. The twin earthquakes struck northwest Iran on magnitude scales of 6.4 and 6.3 Richter. The two earthquakes were separated by 11 min [1]. The earthquakes were strong enough to destroy 70-90 % of 100 villages, with 20 villages disappearing completely [2]. These twin earthquakes were disastrous events with significant medical and psychosocial consequences.At the night of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Both RRs- and ERs-performed FASTs had about 60% sensitivity and 99% specificity in comparison to the final outcome based on the findings of abdominal CT scans and clinical follow-up ( 21 ). Kakaei et al evaluated the role of FAST in assessing injured people in Iran 2012 earthquake and reported that sensitivity of FAST did not change when it was performed by RRs, but its specificity increased (compared to EM and surgery residents) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both RRs- and ERs-performed FASTs had about 60% sensitivity and 99% specificity in comparison to the final outcome based on the findings of abdominal CT scans and clinical follow-up ( 21 ). Kakaei et al evaluated the role of FAST in assessing injured people in Iran 2012 earthquake and reported that sensitivity of FAST did not change when it was performed by RRs, but its specificity increased (compared to EM and surgery residents) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kakaei et al examined the use of FAST in the 2012 Iranian earthquake. 26 Emergency physicians and surgery residents performed FAST, and nearly all of these ultrasounds were repeated by radiology residents and then subsequently were followed by CT results, clinical course, DPL, and surgical findings. These studies were all performed in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…During periods of high patient influx, FAST was used to assess and triage patients after Hurricane Katrina, 9/11 in New York, Lebanon War in 2006 and Iran earthquake in 2010 …”
Section: Resultsmentioning
confidence: 99%